Pengaruh Pengetahuan Dan Pemanfaatan Teknologi informasi Terhadap Efektivitas Sistem Informasi Akutansi Pada Dinas Kehutanan Provinsi Sumatera Utara - Sri Madinah Daulay; Indra Fauzi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Sumatera Utara)
The purpose of this study was to determine: 1) To determine the effect of knowledge of the accounting department employees on the effectiveness of accounting information systems at the Forestry Service of North Sumatra Province., 2) To determine the effect of the use of information technology on the effectiveness of accounting information systems at the Forestry Service of North Sumatra Province, . 3) To determine the effect of simultaneous knowledge of accounting employees and the use of information technology on the effectiveness of accounting information systems at the Forestry Service of North Sumatra Province. This research was conducted using quantitative methods. The variables used are information technology knowledge of accounting employees, utilization of information technology and effectiveness of accounting information systems. The study was conducted to determine the effect of the independent variables on the dependent variable partially or simultaneously. The results of this study indicate that: 1) Partially, the accounting information technology knowledge of employees (X1) has a significant positive effect on the Effectiveness of Accounting Information Systems, 2) partially, the Information Technology Utilization variable (X2) simultaneously has a significant positive effect on Effectiveness of Accounting Information Systems, 3) Simultaneously the variable on the Knowledge of Accounting Information Employees (X1) and the variable of Information Technology Utilization (X2) Simultaneously has a significant positive effect on the effectiveness of the Accounting Information System.